Inovasi Tanggungjawab Sosial Korporasi Sebagai Strategi Bisnis Terhadap Pasar Bagian Bawah Piramida Dan Kemiskinan - Sihombing, Haeryip; Safarudin, Mochamad (Jurnal Administrasi Bisnis, 2009)
Mostly corporate social responsibility activities are programs generated that have nodirectly beneficial impacts to the business. In fact, those activities are merely thespace of philanthropy, so the business core existence as a profits seeker missed out totreat the market as a potential beneficial and advantage. The corporate social responsi-bility, however, which is mixed and derived by two-sided market, localization, buyingmode, and strategy value based, will drive the bottom of pyramid as a potential marketof the competitive advantage for companyâs economic sustainable development andlong-term profits. In case of poverty (TKI), the companies can perform a strategybusiness for economic prospect and development through business innovation and/orinnovation of corporate social responsibility, and vice versa.Keywords: CSR, the bottom of pyramid, 2-sided market, localization, and compet-itive advantage